The relationship between intellectual curiosity and learning engagement in mathematics among adolescents: an analysis of chain multiple mediating effects - Wang, Yongzhao; Zhou, Lijun; Xie, Bingqing; Wang, Lisha; Su, Qiantong; Jin, Hua (Frontiers in Psychology, 2026)
IntroductionLearning engagement (LE) is a core determinant of academic achievement and educational quality.MethodsBased on PISA 2022 data and focusing on a sample of adolescents in Korea (N = 6,308), the current study attempts to investigate how intellectual curiosity (IC) is associated with LE through multiple indirect pathways involving teacher support, encompassing universal, targeted, accompanying, and ongoing teacher support (UTS, TTS, ATS, OTS), and school belonging (SB).ResultsThe significant correlations were demonstrated of varying strengths among IC, UTS, TTS, ATS, OTS, SB, and LE. Further analysis indicated that IC not only influences LE directly, but also exerts indirect effects through UTS, TTS, ATS, OTS, and SB. Specifically, TS and SB exhibited both multiple parallel and multiple chain mediating effects in the relationship between IC and LE, thereby extending the self-determination theory. Additionally, subgroup analyses revealed that the mechanism exhibited significant and distinct divergence along the gender dimension. For instance, males reported a lower perception of TTS, whereas females' LE is more strongly shaped by the indirect effects of TS and SB.DiscussionThese findings elucidate the complex mechanisms how IC affects LE, validate the four-dimensional structure of TS to extend SDT, offer a gender-sensitive intervention perspective for differentiated teaching, as well as provide practical insights for the holistic development of adolescents.